Analysis Of The Influence Of Customer Experience On Repurchase Intention - Rahmadani, Nofela Nidia; Alim, Syahrul (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
In Indonesia, culinary businesses are very easy to find. Indonesia offers many local dishes and a variety of unique menus. One of them is Mie Gacoan. One of the factors that influences someone to make repeat purchases is the customer experience they get from themselves or others. However, the experience that Mie Gacoan Cikarang Branch provides to consumers is a bit slow due to the long queues and some consumers always make repeat purchases. This research will examine the influence of customer experience dimensions on consumers repurchase interest. There were 100 respondents in this research, namely consumers of Mie Gacoan Ciakrang. This research is quantitative and uses SPSS analysis tools. From the data processing that has been carried out, it is known that customer experience partially has a positive and significant effect on repurchase interest in Mie Gacoan Cikarang